Frugal innovation hijacked: the co-optive power of co-creation - Tesfaye, Linda Annala (Journal of business ethics, 2022)
In this paper we investigate how different discourses on frugal innovation are articulated, and how the dynamics between these different discourses have led to a certain dominant understanding of frugal innovation today. We analyse the dynamic interactions between three discourses on frugal innovation: (1) innovations for the poor, (2) grassroots innovations by the poor, and more recently (3) co-creating frugal innovations with the poor. We argue that this latter discourse is articulated as a hegemonic project as it is designed to accommodate demands from both business and poor communities. We draw on Laclau and Mouffe’s concepts of ‘chain of difference’, ‘empty signifier’ and ‘floating signifier’ to explain the advent of the hegemonic discourse on co-creating innovations with the poor. We show how a floating signifier with radical potential, frugal innovation, has been hijacked and co-opted in a hegemonic project that has leveraged powerful ambiguous signifiers, with co-creation acting as an empty signifier. To clarify what is problematic in this hegemonic intervention, we expose how contemporary frugal innovation discourse contributes to a project of governing and exploiting rather than helping the poor, in ways that benefit formal economic actors while further worsening global inequalities.